KELOMPOK PENGRAJIN GERABAH BERBASIS HEALTH CARE - Zainuddin, Zainuddin; Pratama, Koernia Nanda; Wahyudin, Wahyudin (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2021)
Abstract The activity area is in Soreang Ca'di, precisely in Pa'batangan Village, Mappasunggu District, Takalar Regency. In Soreang Ca'di village there are several groups of pottery craftsmen who are currently actively producing several types of pottery. This activity aims to increase the knowledge of craftsmen about personal protective equipment while at work, there are guidelines that become a reference for craftsmen in protecting themselves during work. The method used in this activity is counseling and training with simulations with an active participation approach. Based on the results of the activities that have been carried out, it can be seen that the counseling and training carried out have increased the knowledge of craftsmen. Conclusion: The counseling and training carried out effectively increased the knowledge and behavior of Posyandu craftsmen in washing hands and using PPE in making pottery craftsmen. Keywords: Craftsmen, Pottery, Knowledge, Behavior